Table of Content - - (Journal of Curriculum and Teaching Methodology, 2024)
Table of Content 1. Evaluating the Distance Learning Experience Provided to Students with Special Needs in Saudi Arabia from Teacher’s Viewpoints Mrs. Fatimah Hamad Aldoseri, Dr. Manal Abdulrahman Almuhanna 2. The Effectiveness of a Program Using Modeling Learning Strategy in Developing Self-Esteem in Early Childhood Mrs. Kady Mohammed Abdullah Al Assaf 3. Effectiveness Lesson Study-Based Professional Development on developing teaching self-efficacy of mathematics teachers in the Sultanate of Oman Dr. Nasser Saed Alnbouri, Dr. Mohammed Saed Alghafri 4. Employing Educational Games in Teaching Mathematics to Low-Achieving Third-Grade Students: Perspectives of Their Teachers in UNRWA Schools in Ramallah Reem Mashhour Jawabreh, Nimah Nael Nimer, Maram Raed Mazara, Donia Azzam Abu Sharbak, Rahaf Saleh Sarsor 5. Self-organized Learning and its Relationship to Positive Thinking and Problem-solving among Taif University Students Mrs. Ghadeer Abdullah Ayed Al-Otaibi